1980
DOI: 10.1073/pnas.77.8.4439
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of anion binding sites on cytochrome c by differential chemical modification of lysine residues.

Abstract: The carbonate binding site on horse cytochrome c was mapped by comparing the yields of carboxydinitrophenyl-cytochromes c, each with a single carboxydinitrophenyl-substituted lysine residue per molecule, when the modification reaction was carried out in the presence and absence of carbonate. The site is located on the "left surface" of the protein and consists of lysine residues 72 and/or 73 as well as 86 and/or 87 (Carbonate Site). Although one of the binding sites for phosphate on cytochrome c (Phosphate Sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 31 publications
5
36
0
Order By: Relevance
“…Because of the relatively high PI = 10.04 of cytochrome c, the proteincarriesanetpositivechargeatpH7(Z=+7.1atpH7.15 and p = 0.1 [Shaw & Hartzell, 19761). This would give rise to an electrostatic attraction for anions, and the protein is known to bind anions, including chloride (Stellwagen & Babul, 1975;Taborsky & McCollum, 1979;Osherhoff et al, 1980). Electrostatic interactions would release electrostricted water, which would cause a net rise in volume (Cohn et al, 1934;Cohn & Edsall, 1943).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the relatively high PI = 10.04 of cytochrome c, the proteincarriesanetpositivechargeatpH7(Z=+7.1atpH7.15 and p = 0.1 [Shaw & Hartzell, 19761). This would give rise to an electrostatic attraction for anions, and the protein is known to bind anions, including chloride (Stellwagen & Babul, 1975;Taborsky & McCollum, 1979;Osherhoff et al, 1980). Electrostatic interactions would release electrostricted water, which would cause a net rise in volume (Cohn et al, 1934;Cohn & Edsall, 1943).…”
Section: Resultsmentioning
confidence: 99%
“…It would also suggest that CUA may be relatively close to the surface of subunit II. The haem edge of cytochrome c is surrounded by a cluster of lysine residues that are essential in binding (Osheroff et al, 1980). Interaction between these and the carboxylic residues on subunit II might assist in docking cytochrome c to its binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Steady-state kinetic studies revealed that the reaction rate was limited by product dissociation at low ionic strength, reached an optimum at intermediate ionic strength, and was strongly inhibited at high ionic strength, indicating a significant electrostatic interaction between the two proteins (1)(2)(3)(4)(5)(6). Extensive chemical modification studies have shown that six or seven highly conserved lysine amino groups surrounding the heme crevice of cytochrome c are involved in the electrostatic complex with cytochrome oxidase (7)(8)(9)(10)(11)(12)(13)). An early carbodiimide modification study provided evidence that four carboxylate groups on subunit II of cytochrome oxidase might be involved in the electrostatic interaction with cytochrome c (14).…”
mentioning
confidence: 99%